AN ANALYSIS OF THE EMOTIONAL EXPRESSIONS IN THE SELECTED SONGS OF THE ALBUM “BLONDE” BY FRANK OCEAN - Ahmad, Ahmad; Mahmud, Murni; Burhamzah, Muftihaturrahmah (State University of Makassar, 2025)
In this study, the researcher analyzed the emotional expressions in three selected songs from Frank Ocean’s Blonde album, namely Ivy, Self-Control, and Godspeed. The research applies Parrott’s (2001) theory of emotions, which categorizes emotions into three levels: primary, secondary, and tertiary. A descriptive qualitative method was used to identify the emotions conveyed in the song lyrics.The findings show that the lyrics depict various emotions. Primary emotions, such as surprise and sadness, arise from spontaneous reactions. Secondary emotions, like hope and longing, are revealed through deeper reflections. Tertiary emotions, which are more complex, reflect emotional maturity and acceptance, as seen in the lyric